Comparative study of transdermal nitroglycerine patch vs. intramuscular isoxsuprine in treatment of preterm labour - Kokane, Abhijeet; Sonawane, Pundalik (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Preterm labour and delivery are very challenging obstetric complications encountered by obstetricians. Despite advances in perinatal medicine, the incidence continues to increase.so need for best tocolytic is necessary to reduce perinatal mortality associate with preterm birth. Methods: A randomized prospective comparative study, carried out over a period of 24 months.100 antenatal cases with 24-36 weeks of gestation randomly selected & divided into two groups of 50 each. Group A: Treated with transdermal nitroglycerine patch (NITRODERM TTS-10 patch releasing 10mg / 24hr till 48 hrs.) & Group B : Treated with intramuscular isoxsuprine (Inj). Duvadilan 10 mg / 8 hrly till 48 hrs.) after treatment in both groups Patients started on capsule Duvadilan retard (40mg) OD for one more week. Data collected regarding efficacy of the drugs in terms of Maternal side effects, Fetal side effects, prolongation of pregnancy for (48 hrs/ 48-72 hrs/3-7 days/>7 days), Changes in cervical dilatation and cervical length after 48 hrs, Mode of delivery, Gestational weeks at the time of delivery, Neonatal outcome. Results: In our study there was no statistically significant difference in demographic data, risk factors, gestational age at admission, obstetric score, fetal side effects, prolongation of pregnancy, cervical length changes, successful tocolysis, gestational age at delivery, mode of delivery, neonatal outcome But Mean cervical dilatation changes after 48 hrs. of tocolytic treatment in these two groups were statistically significant (0.14 vs. 0.19, p value = 0.024) where nitroglycerine is more effective. Headache was exclusively seen in 80% patients of nitroglycerine group & tachycardia and palpitation exclusively seen in 88% patients of isoxsuprine group, where difference is statistically significant (p value = 0.0001). Conclusions: Nitroglycerine patch should be recommended over intramuscular isoxsuprine for all preterm labour patients including threatened preterm as it appears to be better tolerable in term of treatable side effect & better acceptable than painful multiple intramuscular injections of isoxsuprine.